Significado e dor no esporte de alto rendimento - Caetano, Juliana Naves Neves (2012)
This paper describes the perceptions and meanings of pain for the athlete high performance in light of Symbolic Interactionism perspective. We interviewed 10 athletes who developed his career in elite sport in Brazil. The research was an exploratory, descriptive and data were collected through semi-structured interviews and analyzed qualitatively. Were grouped into categories of themes that stood out. The main result was the perception and the meaning of pain as a social and cultural product, represented and interpreted in accordance with the group and the webs of interaction set by athletes in the sport environment. The way to deal with it will depend on the "definition of situation" of the athlete. The responses to this phenomenon will be particular to each individual and not a purely biological understand all its complexity.